Incident investigation tracking system based on process safety management - Chew, Mann Yee (2018)
Incident investigation is a method to determine root cause of the incident and propose corrective actions to prevent recurrence. It is one of the element under Process Safety Management (PSM) OSHA 29 CFR 1910.119 (m) regulation. Although this regulation established in 1992, some catastrophic process safety accidents still occurred. This is because there are some problems that caused the failure of the implementation of this regulation. People failed to record and document the underlying causes had cause this element failed. Besides that, the proposed corrective actions did not implement properly in most of the cases to prevent recurrence. Furthermore, people unable to learn the lessons from the past incident cases as the incident investigation reports are difficult to be accessed. Even though the incident reports are able to access, the information in the report may incorrect as the organisation may alter the information in order to protect its privacy. Some information are missed out as there is no proper tool to aid this complex incident investigation procedures. Thus, this study is about the development of a full incident investigation tracking system to ease the implementation of PSM program. An improved framework is developed by arranging the requirements during an incident investigation and organising the incident investigation steps accordingly. Then, the framework is loaded into Microsoft Access to form an incident investigation tracking system. After the tracking system is completed, it is verified with two case studies. If there are lack of the required information in the case studies, the tracking system will prohibit the user to proceed to the following steps as this is the gap in the incident investigation report.